Stages of Learning and Progression in Mathematics - Krupa, Tatiana V. (The journal of contemporary issues in business and government, 2021)
There is not a country in the world which functions without supplying its schools with teaching content for every grade. This kind of syllabus is called “curriculum”. It is essential to define grade expectations which should fulfill three chief objectives: pinpointing important teaching content, characterizing learning progression which, if properly implemented, will enable students to get ready for professional life and coordinating various mathematical topics. Teachers face a huge variety of learning methods for their students while choosing concrete topics for different grade levels. There can bedifferent (either low or high) expectations for grade levels of student preparation. Efficient teaching should always comply with learner’s intellectual abilities. Thus, implicit contradiction between meeting grade level expectations and satisfying the personal requirements of students in inevitable. The connection between knowledge and possible grade expectations leads to certain dilemma which includes both subjective and objective points of view. The general aims of the Education 2030 project are about solving this discrepancy.